Proceedings of the 22nd International Conference on Paste, Thickened and Filtered Tailings 2019
DOI: 10.36487/acg_rep/1910_11_thomas
|View full text |Cite
|
Sign up to set email alerts
|

Earth observation data and satellite InSAR for the remote monitoring of tailings storage facilities: a case study of Cadia Mine, Australia

Abstract: Tailings storage facilities (TSFs) are an essential infrastructure of mineral processing, but they represent a significant physical, chemical and biological hazard and must, therefore, be strictly and responsibly sited, managed and closed. Tailings can, for example, be dispersed by many processes (such as sinkholes, earthquakes, intense rainfall and flood events, and wind), substandard design and construction, and seepage. The stability and behaviour of TSFs needs to be continuously monitored and one highly ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 1 publication
0
11
0
1
Order By: Relevance
“…For example, usually the displacement measurements refer only to a given orientation axis or plane related to the line of sight of the equipment, potentially implying a bias. Also, authors state that changes in surface conditions -for example, moisture, temperature, and especially vegetation -may lead to significant noise and errors in measurements (Thomas et al, 2019;Robertson, et al, 2019, Gama, et al, 2013.…”
Section: Discussionmentioning
confidence: 99%
“…For example, usually the displacement measurements refer only to a given orientation axis or plane related to the line of sight of the equipment, potentially implying a bias. Also, authors state that changes in surface conditions -for example, moisture, temperature, and especially vegetation -may lead to significant noise and errors in measurements (Thomas et al, 2019;Robertson, et al, 2019, Gama, et al, 2013.…”
Section: Discussionmentioning
confidence: 99%
“…This poses a difficult challenge to significantly reducing tailings dam failures; hence, there is an acute need to monitor junior mining operations (Lumbroso et al 2019). Recent work has shown that a low-cost tool, which uses EO-based information, could help improve the capacity of environmental regulators and non-governmental organisations (NGOs) to monitor tailings by improving their oversight of both large and small mines (Chetty 2013;Hui et al 2015;Thomas et al 2019).…”
Section: Types Of Tailing Dams and Their Potential Problemsmentioning
confidence: 99%
“…In particular, case studies on the use of satellite InSAR to analyze mining-induced slope instabilities are scarce, as most of them focus on ground subsidence (e.g., [16][17][18]). Nevertheless, the application of such technique has been documented in a few mining sites in Australia [19,20], Brazil [21,22], Spain [23,24], South Africa [15], Turkey [7], and U.S.A. [14,25]. However, in most cases these works present analyses of the InSAR data at the slope scale, or include no complementary stability analyses taking into account geotechnical data through geo-mechanical modeling.…”
Section: Introductionmentioning
confidence: 99%